Local communities' perceptions of climate variability in the Mt. Elgon region, eastern Uganda - Bomuhangi, Allan; Nabanoga, Gorettie; Namaalwa, Justine J.; Jacobson, Michael G.; Abwoli, Banana (Informa UK Limited, 2016)
In order to develop climate adaptation strategies that address location and context-specific vulnerabilities, there is need to understand how communities perceive the variability in their climate as perception of climate variability is a critical component within which climate adaptation should operate. This paper examines communities’ perceptions about climate variability in relation to available meteorological data in the Mt. Elgon region. The study demonstrates that community perceptions of temperature and precipitation trends as indicators of climate variability are in agreement with meteorologically observed trends. It also reveals that local communities’ perceptions of climate variability may also provide more localized contexts of climate variability which be insufficiently captured by meteorological data in communities where capture of meteorological data is not fully developed.